Value-based utility adaptation of RED parameters - Villacorta, Rachel P. (2005)
Random Early Detection (RED) is a congestion avoidance mechanism in routers wherein the average queue is compared to the minimum and maximum thresholds of a router's buffer. This range is used to determine whether packets are dropped, marked for later dropping, or allowed to pass depending on the size of the queue relative to the thresholds. RED is effective in decreasing loss rates of responsive flows but performs poorly with User Datagram Protocol (UDP) traffic since these do not react to congestion notification. It is important to address UDP flows' requirements since UDP traffic are used in applications such as streaming video and audio which form a considerable part of Internet traffic. This thesis shows the use of Value-Based Utility (VBU) with RED to manage UDP flows. VBU provides additional information which allows packet dropping end enqueing decisions to be more sensitive to UDP traffic packet loss requirements. Three RED variations incorporating VBU were developed. the first uses VBU to aid RED's decision on whether to drop or enqueue a packet when the average queue size is between the thresholds. The second solution logically partitions the buffer to allocate space for each type of flow while utilizing VBU to differentiate requirements of flows. Lastly, the maximum threshold of each logically partitioned buffer is adapted in response to the utility values obtained from VBU. Results indicate adoption of VBU with RED enhances management of UDP traffic. This results in the equitable distribution of loss based on the UDP flows' requirement.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Communication and traffic; Computer networks -- Management; Computer networks -- Quality control; Computer network protocols; Packet-switching (Data transmission).